Validity of Hand Held Fundus Camera by Optometrist using Slit lamp 90 d bio microscopy as a reference standard for screening of Diabetes Retinopathy - Ahsan, Shahid; Haseeb, Uzma; Memon, Muhammad Saleh; Bukhari, Sadia; Mahmood, Tauseef; Fahim, Muhammad Faisal (Journal of the Pakistan Medical Association, 2022)
Objective: To find out the validity of hand-held fundus camera by optometrist using slit lamp 90D biomicroscopy as reference standard for screening of diabetes retinopathy. Method: The observational cross-sectional study was conducted at the diabetic clinic of Al-Ibrahim Eye Hospital, Karachi, from August 2020 to May 2021, and comprised diabetics of either gender aged >16 years visiting the outpatient department. Un-dilated fundus photograph of both eyes were taken with non-mydriatic fundus camera. Pupils were then mid-dilated with one drop of tropicamide 1% before capturing retinal images by handheld fundus camera by another optometrist. Both the optometrists identified and recorded the presence and absence of diabetic retinopathy. Subsequently, a retinal specialist examined the fundus with slit lamp 90 D biomicroscopy. Data was analysed using SPSS 23. Results: Of the 500 subjects, 291(58.2%) were males and 209(41.8%) were females. The overall mean age was 54.49±9.16 years (range: 16-83 years). Of the 1000 eyes, fundus was not readable in 130(13%) by hand-held fundus camera, 296(29.6%) eyes by non-mydriatic fundus camera and 76(7.6%) eyes by slit lamp. Sensitivity and specificity of hand-held fundus camera compared to non-mydriatic fundus camera was 89.86% and 80.36%, respectively. In comparison with slit lamp, the sensitivity was 91.71% and specificity was 71.10%. Kappa statistic for diabetic retinopathy detection by hand-held fundus camera versus non-mydriatic fundus camera was 0.705, indicating substantial agreement. Kappa statistic for diabetic retinopathy detection with hand-held fundus camera versus slit lamp (standard) was 0.609, indicating good agreement. Conclusion: Handheld fundus camera with semi-dilated pupil was found to be a valid screening tool in the hand of optometrist for preliminary screening of diabetic retinopathy. Key Words: Retinal screening, Hand-held fundus camera, Optometrist, Sensitivity, Specificity.